The influence of social capitalism on construction safety behaviors: An exploratory megaproject case study - Wu, X.; Chong, Heap Yih; Wang, G.; Li, S. (M D P I AG, 2018)
Health and safety issues are critical factors influencing the sustainable development of mega construction projects. The impact of social capitalism on health and safety activities has been widely discussed in sustainability domains; nevertheless, its influence towards workers' safety behaviors in mega construction projects remains largely unknown. To address this research gap, the current study aims to determine the influence of social capitalism on safety behaviors from a two-fold perspective between project managers and construction workers. An exploratory case study was adopted from a mega construction project in Tianjin, China. The results reveal that (a) the social network between project managers and construction workers manifests itself as close communication and contact, trust and emotional identification, common language, vision, and values; (b) project managers' management behaviors show stronger influences on construction workers' safety compliance behaviors, while their leadership behaviors show stronger influences on construction workers' safety participation behaviors; and (c) the practice of social capitalism promotes enforcement of commands and compulsory norms and plays a positive regulatory role on safety behaviors. These findings provide new insights into the use of social capitalism for improving safety behaviors and ultimately facilitate the attainment of the broader goal of sustainability in mega construction projects.